A Study of the Honduran and Colombian Coffee Industry Competitiveness: A Porter’s Diamond Approach - Hernandez B., Engell R. (Zamorano: Escuela Agrícola Panamericana, 2023)
Coffee is one of the most widely consumed beverages globally, with significant cultural and social significance in many countries. Colombia and Honduras are known as two of the largest coffee-producing countries. This paper aims to describe the factors that have led Colombia to be one of the top three coffee producers in the world, elements that will serve as a benchmark for developing the Honduran coffee sector. The paper examines the competitiveness of the coffee industries in Honduras and Colombia using Porter’s Diamond Model. This model revealed the comparative advantage index of both countries to measure their comparative advantage in the coffee sector in the global market. The study results showed that Honduras has a higher comparative advantage in the international market than Colombia. However, both countries have areas for improvement. The study determined that both countries have favorable production factor conditions (land and labor). However, in terms of infrastructure, Honduras has better port infrastructure than Colombia. It was found that Colombia has a larger market due to its larger population, more robust marketing, better logistics infrastructure, and lower levels of corruption. Both countries have supporting solid industries and well-established institutions supporting the R&D. Based on the findings, some recommendations for the Honduran coffee industry are to improve its productivity, yield, and working conditions. Also, it is necessary to invest in advanced tracking and tracing technologies. Overall this paper provides valuable insights into both countries’ coffee sectors, which can be used by policymakers, industry stakeholders, and coffee producers to make informed decisions.